PHENOMENOLOGY STUDIES: INTERPRETING THE BUDGET DEFICIT OF THE STUDY PROGRAM - Suheriyatmono,; Carmel Meiden,; Elisabeth Vita, (International Journal of Social Science, 2022)
The focus of this research is to interpret the budget deficit of the study program. Budget deficits in study programs are a problem that disrupts sustainability. Budget deficits have always been seen from the financial side which is interpreted as spending greater than receipts. The occurrence of deficits in the study program has been going on for a long time. But there are differences in perception between the foundation and the head of the study program. The research site takes place in the study program of educational institutions in Lampung. The research informants numbered three people. The research took place from the 20xx budget year to 20xy. The definition of the budget deficit is in the form of: suffering. Reconstruct the meaning of the budget deficit in the form of 'lantern' leaders to serve, prosper and glorify.